Pembangunan Sistem Informasi Layanan Kemahasiswaan Berbasis Web Menggunakan Service-Oriented Architecture - Fikri Septrian Anggara; Lutfi Rahmatuti Maghfiroh (Politeknik Statistika STIS, 2022)
The Academic and Student Administration Section (BAAK) is one of the implementing elements of the STIS Statistics Polytechnic administration and has responsibilities, one of which is student services. The service process in the student affairs department is still done manually, for example in the Data Request Letter (SPD) and Student Certificate (SKM) services. Service requests are made via email or directly in the BAAK room, the service request review process has not been computerized so that it is prone to errors and is not efficient and the approval progress is not monitored by the user. This study aims to design and build a progressive web-based student service information system with the hope of being able to meet the needs of BAAK's student business processes. The development of this information system is carried out using the modified eXtreme Programming method and RESTful MSOAM. Based on the evaluation results, it is known that the system has implemented the proposed business processes for SPD and SKM services, has met 90.77% of the acceptance criteria for user requirements, has met PWA requirements, and has met the 4 core principles of service-orientation and the principle of reusability.